ShenQi FuZheng injection as an adjunctive treatment to chemotherapy in breast cancer patients: a meta-analysis - Hongbo Zhang; Tingting Chen; Lizhu Shan (Taylor & Francis Group, 2019)
Context: Shenqi FuZheng injection (SFI) has been suggested as a complementary treatment of chemotherapy in China. However, little is known about it in western countries. Objective: This study assesses the clinical effect of SFI combined with chemotherapy for breast cancer patients. Materials and methods: Both English and Chinese databases were searched covering the time period of 1999- 2018 for relevant studies comparing the effect of SFI plus chemotherapy treatment with chemotherapy alone in patients with breast cancer. Target outcomes concerning treatment effect, performance status, immune system and toxic effects were extracted and combined using Stata version 15.0 software. Quality assessment was performed using the Jadad scale. Results: Forty-nine trials were included based on certain selection criteria. Only seven studies were rated as high-quality publications. Results of meta-analysis showed that SFI intervention can significantly improve objective tumour response, performance status, NK, CD3+, CD4+ and CD4+/CD8+ ratio and reduce occurrence of leucopenia, thrombocytopenia, haemoglobin reduction, liver dysfunction, gastrointestinal reaction, nausea and vomiting, bone marrow suppression and ECG changes. However, no significant difference was found between SFI and the control group regarding CD8+ levels, and renal disorders. Discussion and conclusions: SFI intervention appeared to be effective in improving clinical efficacy, immune function and reducing toxicity when combined with chemotherapy for breast cancer. However, our findings still need verification by high-quality trials.